قبل ازولادت نبوی مباحث سیرت تفسیر روح المعانی کی روشنی میں: Sira Discussions Befofe Prophet(Peace be upon him) 's BIrth in Tafsir Roh ul M'ani - واحد محمود،ڈاکٹر محمد عاطف اسلم راوٰ (Seerat Studies, 2024)
Biography of the Prophet (peace be upon him) is a comprehensive guide to every aspect of life, including beliefs, worship, routines of daily life, economics and so on. For the need for a rectified society, Islamic scholars have always set forth Sīrah to play a practical role. Thus, scholars have compiled numerous books on Sīrah. ‘AllāmaAalōsī possesses a significant position among the outstanding scholars of Islam. His commentary Rōh ul M‘ānī, Tafsīr al-Qur‘ān al-Karīmwa'l-Saba walMuthānī, is a beautiful blend of the spiritual guidance of the Holy Qur‘ān and presentation of diverse aspects of Sīrah. This research is aimed to explore the contributions of ‘AllāmaAalōsī in the field of Tafsīr and Sīrah as he attained a distinct dignity as one of the best reformers and Mufassir in the history of Islam. Utilizing analytical and historical research methodology, the article presents all those significant events and references that occurred before the birth of the Holy Prophet (peace be upon him).